2021
DOI: 10.31186/jspi.id.16.3.277-282
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Imported Beef in Indonesia

Abstract: Imported beef cattle are cattle (not breeds) imported from abroad to Indonesia, which have superior characteristics to be kept for a certain period to produce meat. The purpose of this research is to explore the quality of imported beef cattle entering Indonesia. The object of the research is beef cattle Breed Brahman Cross, Heifers type as many as 331 heads imported from Australia. The variables observed were Arrival weight (AW), Reweigh (RW), Selling Weight (SW), Weight Difference (WD), Fattening Duration (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Sawdust and cocodust was utilized as bedding, which is regularly cleaned and changed every 14 days. This practice was similar with previous study [11]. Based on the observation in three feedlots, the production flow of beef cattle fattening can be summarized as presented in Figure 3.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Sawdust and cocodust was utilized as bedding, which is regularly cleaned and changed every 14 days. This practice was similar with previous study [11]. Based on the observation in three feedlots, the production flow of beef cattle fattening can be summarized as presented in Figure 3.…”
Section: Resultssupporting
confidence: 70%
“…Initial body weight in surveyed feedlots was almost the same. Previous study showed that the early period of cattle arrival typically results in weight loss, resulting in a difference in weight when reweighed [11]. Stress experienced by animals during transportation has an impact on this condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, most of Indonesia's cattle imports are imports from Australia; livestock imports are intended to increase the added value of beef cattle farming businesses in Indonesia [19]. The choice of Australia as the main source of cattle imports is due to the relatively close distance between Indonesia and Australia so that consumption of fresh meat can be fulfilled, considering that consumers in Indonesia prefer fresh meat to frozen meat.…”
Section: The Growth Of Consumption Production and Import Of Beef In I...mentioning
confidence: 99%